1984
DOI: 10.1007/bf01820886
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the basement complex in the central eastern desert of Egypt

Abstract: With 2 figures ZusammenfassungDie Gesteine des /igyptischen Kristallins sind in drei Hauptgruppen unterteilt: Meatiq Group (/ilteste), Abu Ziran Group und Hammamat Group (jiingste); die letzten zwei Gruppen geh6ren dem Pan-Afrikanischen Zyklus an. Die Meatiq-Gruppe stellt einen alten Sokkel dar, der in Gneisdomen auftritt. Die Abu-Ziran-Gruppe umfaBt die Geosynklinal-Assoziation, die aus einer unteren ophiolitischen Einheit besteht, iiberlagert von Sedimenten, volkanoklastischen Sedimenten und lokalen intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(62 citation statements)
references
References 20 publications
0
62
0
Order By: Relevance
“…The Quaternary rocks are composed of wadi and terrace deposits consisting of detritus sand, pebbles, and rare boulders. The mountainous central zone consists of the basement rocks, intensively studied by many authors like Hume (1935), El-Ramly (1972), El Gaby et al (1984, El Shazly (1964), El Ramly (1960), andEl-Ramly et al (1970). They concluded that the mountainous areas are essentially composed of panAfrican assemblages comprising gneisses, migmatites, metasediments, ophiolitic melanges, metavolcanics, mafic intrusions, tonalite, granodiorite, younger volcanics, molasse sediments, post-tectonic granites, and trachyte plugs and sheets.…”
Section: Study Areamentioning
confidence: 99%
“…The Quaternary rocks are composed of wadi and terrace deposits consisting of detritus sand, pebbles, and rare boulders. The mountainous central zone consists of the basement rocks, intensively studied by many authors like Hume (1935), El-Ramly (1972), El Gaby et al (1984, El Shazly (1964), El Ramly (1960), andEl-Ramly et al (1970). They concluded that the mountainous areas are essentially composed of panAfrican assemblages comprising gneisses, migmatites, metasediments, ophiolitic melanges, metavolcanics, mafic intrusions, tonalite, granodiorite, younger volcanics, molasse sediments, post-tectonic granites, and trachyte plugs and sheets.…”
Section: Study Areamentioning
confidence: 99%
“…These occur in antiformal, 'domal' positions, generally surrounded by lower grade supracrustal assemblages (see summary in Greiling et al, 1994). In the ED such rocks occur at Meatiq (Sturchio et al, 1983;E1-Gaby et al, 1984;Habib et al, 1985;Bennet and Mosley 1987), in three distinct domal structures at Hafafit (Greiling and ElRarely, 1990;Rashwan, 1991) and in the region along Wadis Bitan and Haimut (Geological Map 1:500 000, sheet NF 36 NE Bernice, Technische Fachhochschule Berlin 1987). In south-western Sinai similar rocks occur in the Wadi Feiran region (E1-Gaby and Ahmed, 1980;Shimron, 1980).…”
Section: Introductionmentioning
confidence: 97%
“…The two first authors speculated that the granitoid gneisses were younger than the low-and medium-grade supracrustals surrounding the gneisses, whereas Sabet (1961) consider all the mafic rocks (both volcanics, metasediments and amphibolites) to be part of one supracrustal sequence. El-Gaby (1994) and El-Gaby et al (1984) advocated the idea that the gneisses in the Meatiq, Hafafit and El-Sibai domes were all pre-Neoproterozoic infrastructural rocks exposed in the hinge zone/core of one or more NW-trending antiform(s). The structural model proposed by El-Gaby et al (1984) may be correct, but the protolith age proposed for the gneisses finds little support in the emerging body of new isotope and geochronological data from CED (e.g.…”
Section: Geology Of the El-sibai Areamentioning
confidence: 99%
“…El-Gaby (1994) and El-Gaby et al (1984) advocated the idea that the gneisses in the Meatiq, Hafafit and El-Sibai domes were all pre-Neoproterozoic infrastructural rocks exposed in the hinge zone/core of one or more NW-trending antiform(s). The structural model proposed by El-Gaby et al (1984) may be correct, but the protolith age proposed for the gneisses finds little support in the emerging body of new isotope and geochronological data from CED (e.g. Andresen et al 2009;Liégeois and Stern 2010).…”
Section: Geology Of the El-sibai Areamentioning
confidence: 99%
See 1 more Smart Citation